(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
The integration of robotic servers, known as Jollibots, at Jollibee Glorietta 4 has enhanced operational efficiency and attracted customer attention. However, this technological innovation also presents challenges. These include possible technical malfunctions that may result in service delays or order errors, which necessitate routine maintenance and reliable technical support. Additionally, the absence of human interaction may affect customer satisfaction, highlighting the need to balance automation with personalized service. The rise of automation also raises concerns about job displacement. Nevertheless, these can be addressed through employee retraining and upskilling programs. A hybrid service model, where Jollibots operate alongside human staff, is proposed to maximize efficiency while maintaining service quality and protecting employment. This study adopts a descriptive-correlational research design to assess the impact of Jollibots on the customer dining experience at Jollibee Glorietta 4. Data will be gathered using a structured questionnaire distributed to customers who have interacted with the Jollibot system. Convenience sampling will be used to select participants from various demographic groups, including age, gender, and visit frequency. The objective is to evaluate customer perceptions of service quality, efficiency, and satisfaction in relation to robotic-assisted dining. The findings revealed that most of the customers at Jollibee Glorietta 4 were aged 18 to 21, with a higher brand preference observed among female respondents. A majority of participants were familiar with the company’s corporate social responsibility (CSR) programs and reported visiting the branch twice a month. Despite the technological advancements, customer satisfaction remained variable. Product and service quality were found to have a limited direct impact on satisfaction, while factors such as friendly staff, prompt service, and cleanliness played more significant roles. Variable cost was also identified as a key determinant of overall dining satisfaction. Additionally, the study noted specific limitations at the Glorietta 4 branch, such as difficulties navigating the ordering system and limited food selections. This study assessed the impact of Jollibots on customer dining experiences and found that robotic service contributes positively to operational efficiency but requires enhancements to meet customer expectations fully. The results suggest that while robotic servers can streamline processes, the absence of human interaction may hinder the overall dining experience. A balanced approach involving both robotic and human service is recommended to address these concerns. Future strategies should focus on improving Jollibot functionality, maintaining service quality, and implementing a hybrid model that prioritizes both technological innovation and human engagement.